Strengthening Instructor Human Resources Through the Problem-Based Learning Model at the Gorontalo Regional Police Academy - Towapa, Halim; Ngiu, Zulaecha; Ahmad, Muchtar (Universitas Pahlawan Tuanku Tambusai, 2025)
Police education in the modern era faces increasingly complex challenges, requiring instructors to have pedagogical and professional competencies that are in line with the values of Tribrata and Catur Prasetya. However, there is still a gap between the ideal of active learning and the practice in the field, which tends to be teacher-centered, where the level of activity and critical thinking skills of students (Serdik) at the Gorontalo Regional Police Academy (SPN Polda Gorontalo) is still low. This study aims to analyze the implementation of Problem-Based Learning in improving the activity and critical thinking skills of Serdik. The method used is descriptive qualitative, with data obtained through interviews, observations, and document analysis. The results of the study show that the application of PBL has begun to change the learning paradigm to be more reflective and participatory, although it still faces challenges in the form of instructor pedagogical readiness, training gaps, and infrastructure limitations. It is concluded that institutional support and continuous development of instructor competencies are the keys to the successful application of PBL in police education.